5/1 • 2/5 = 10/5 = 2
The area is 2 inches
The system is:
i) <span>2x – 3y – 2z = 4
ii) </span><span>x + 3y + 2z = –7
</span>iii) <span>–4x – 4y – 2z = 10
the last equation can be simplified, by dividing by -2,
thus we have:
</span>i) 2x – 3y – 2z = 4
ii) x + 3y + 2z = –7
iii) 2x +2y +z = -5
The procedure to solve the system is as follows:
first use any pairs of 2 equations (for example i and ii, i and iii) and equalize them by using one of the variables:
i) 2x – 3y – 2z = 4
iii) 2x +2y +z = -5
2x can be written as 3y+2z+4 from the first equation, and -2y-z-5 from the third equation.
Equalize:
3y+2z+4=-2y-z-5, group common terms:
5y+3z=-9
similarly, using i and ii, eliminate x:
i) 2x – 3y – 2z = 4
ii) x + 3y + 2z = –7
multiply the second equation by 2:
i) 2x – 3y – 2z = 4
ii) 2x + 6y + 4z = –14
thus 2x=3y+2z+4 from i and 2x=-6y-4z-14 from ii:
3y+2z+4=-6y-4z-14
9y+6z=-18
So we get 2 equations with variables y and z:
a) 5y+3z=-9
b) 9y+6z=-18
now the aim of the method is clear: We eliminate one of the variables, creating a system of 2 linear equations with 2 variables, which we can solve by any of the standard methods.
Let's use elimination method, multiply the equation a by -2:
a) -10y-6z=18
b) 9y+6z=-18
------------------------ add the equations:
-10y+9y-6z+6z=18-18
-y=0
y=0,
thus :
9y+6z=-18
0+6z=-18
z=-3
Finally to find x, use any of the equations i, ii or iii:
<span>2x – 3y – 2z = 4
</span>
<span>2x – 3*0 – 2(-3) = 4
2x+6=4
2x=-2
x=-1
Solution: (x, y, z) = (-1, 0, -3 )
Remark: it is always a good attitude to check the answer, because often calculations mistakes can be made:
check by substituting x=-1, y=0, z=-3 in each of the 3 equations and see that for these numbers the equalities hold.</span>
Answer:
26
Step-by-step explanation:
[(7+3)5-4]/2+3
-To solve this equation you have to use PEMDAS
P- Parentheses
E- Exponents
M- Multiplication
D- Division
A- Addition
S- Subtraction-
- With MD and AS you work left to right of the equation since they are in the same spot. (PE[MD][AS])
Step 1) [(10)5-4]/2+3
- First you do "P," parentheses, so you add 7+3=10
Step 2) [50-4]/2+3
- Next you do "M," multiplication, and multiply 10x5=50
Step 3) [46]/2+3
- Then you do "S," subtraction, and subtract 50-4=46
(FYI: Steps 1-3 were still in the parentheses. We had to start with the parentheses in the parentheses, work PEMDAS, and now we are out of the parentheses and have to work PEMDAS on the rest of the problem.)
Step 4) 23+3
- Now we do "D," division, and divide 46/2=23
Step 5) 23+3=6
- Finally we do "A," addition, and add 23+3=26 so the answer is 26
(FYI: "/" means division)
<span>The answer: b. translated according to the rule (x, y) → (x + 8, y + 2) and reflected across the x-axis
If you make the drawing of the situation you realize the you need a reflection through the x-axis, but first you need to translate the polygon several units to the left and upward.
You can see that all the x-coordinates have increased 8 units, so the solution has to include x + 8.
Also, you see that you have to move the polygon 2 units upward before doing the reflection so the solution has to include y + 2.
So, the answer is (x,y) ---> (x + 8, y + 2) and then reflection across the x-axis.
</span>